Dam-break flow experiments over mobile bed: velocity profile. Issue 1 (2nd January 2019) - Fent, Ilaria; Zech, Yves; Soares-Frazão, Sandra
ABSTRACT: Knowledge of the velocity distribution is key for understanding and modelling any type of flow. For steady flows over fixed beds, theoretical and experimental approaches evidenced a logarithmic law in the inner region, in the vicinity of the bed. For flows over mobile beds or for unsteady flows, the velocity profile progressively adapts to the changing flow conditions. In the present paper, new experiments of dam-break flows over a bed made of coarse sand are presented. Detailed velocity measurements both in the clear water layer and in the moving sediment layer were obtained. The measurements show that a logarithmic velocity profile develops not only in the clear-water layer but also in the upper part of the moving sediment layer, in a similar way to previous observations in steady flow with sheet-flow sediment transport.